Government regulation of the economy during the COVID‐19 epidemic in key countries of the world: a comparative analysis - Krasnopyorov , Petro (Global Prosperity, 2023)
This article analyzes measures of state regulation of the economy adopted by key countries of the world during the COVID‐19 pandemic. The study covers aspects of macroeconomic policies, financial instruments and social measures that were used to overcome the negative effects of the crisis. The article focuses on a comparative analysis of the strategies and effectiveness of measures taken by various countries to ensure the stability of economic development and social protection of the population during the pandemic. The author identifies key factors influencing the choice of specific regulatory measures, such as the economic structure of the country, the level of development of the health care system, as well as internal and external factors that determine the stability of the economic system in crisis conditions. Special attention is paid to the study of the relationship between the effectiveness of government measures and the subsequent recovery of the economy after the end of the epidemic. The results of the analysis can serve as a basis for developing recommendations on optimal strategies of state regulation in conditions of large‐scale crises, such as a pandemic, in order to ensure